2004
DOI: 10.21273/horttech.14.3.0307
|View full text |Cite
|
Sign up to set email alerts
|

Optimum Timing of an Application of Corn Oil and Bacillus thuringiensis to Control Lepidopteran Pests in Sweet Corn

Abstract: Corn oil and Bacillus thuringiensis ssp. kurstaki (Bt) applied directly into the silk channel of a corn ear has been shown to be an effective pesticide against corn earworm, Helicoverpa zea (CEW), and european corn borer, Ostrinia nubilalis (ECB). Field studies were conducted in 2000 and 2001 to determine the influence of application timing on ear quality at harvest. Tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
9
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 4 publications
2
9
0
Order By: Relevance
“…This ubiquity limits the ability to use cultural controls such as crop rotation and increases the pest's adaptability and probability of successful development (Kennedy and Storer, 2000;Olmstead et al, 2016). The oviposition and feeding habits also limit the efficacy of chemical controls (Barber, 1941;Cook et al, 2003Cook et al, , 2004. Plant breeding remains one of the few promising tools for reducing the economic damage caused by corn earworm.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This ubiquity limits the ability to use cultural controls such as crop rotation and increases the pest's adaptability and probability of successful development (Kennedy and Storer, 2000;Olmstead et al, 2016). The oviposition and feeding habits also limit the efficacy of chemical controls (Barber, 1941;Cook et al, 2003Cook et al, , 2004. Plant breeding remains one of the few promising tools for reducing the economic damage caused by corn earworm.…”
mentioning
confidence: 99%
“…Corn earworm is an especially challenging pest for organic sweet corn growers, because few effective management strategies are permissible under the National Organic Program (Cook et al, 2003(Cook et al, , 2004Ni et al, 2011). Organic producers are in particular need of breeding for resistance to corn earworm since the advent of transgenic Bacillus thuringiensis cultivars has supplanted classical breeding for earworm resistance.…”
mentioning
confidence: 99%
“…Seven decades later, the chemical insecticide sprayings engendered a series of negative consequences for sustainable sweet corn production, including the costs associated with the increasing number of the insecticide applications during a crop cycle, and the increased concerns about human health, and long-term ecological impact of intensive insecticide applications on nontarget organisms in agro-ecosystems. Research in the last few decades has examined alternative pest management tactics, including planting dates , corn husk features (Wiseman et al 1977), and silk maysin level (Waiss et al 1979, Snook et al 1993, as well as the application of edible oils on corn ears with fresh silks (Cook et al 2003(Cook et al , 2004, or by using a mixture of oils with microbial insecticides . The recent studies have used edible oils instead of mineral oils that were used in 1930 Ð1940s in the New England states, because certain mineral oils no longer meet the present food safety standard (Jackson et al 2007).…”
mentioning
confidence: 99%
“…The Kerr Center for Sustainable Agriculture (KCSA) in Oklahoma and R. Hazzard of the University of Massachusetts Cooperative Extension began conducting experiments in the 1990s using oil silk treatments, combined with Bacillus thuringiensis spp. kurstaki (Bt) products in an effort to develop an organic management technique for CEW on small commercial farms (Cook et al, 2003(Cook et al, , 2004.…”
mentioning
confidence: 99%
“…Oils applied to corn can damage the plant tissues if applied in a high enough dose (Hazzard, 1998). The efficacy of oil treatments has been demonstrated in some experiments, but phytotoxicity or damage to the developing ear from reduced pollination quality as a result of these applications is not well documented (Cook et al, 2003(Cook et al, , 2004Hazzard, 2003). Early experiments by the authors found up to 88% cone-tip injury due to corn oil + Bt treatments (T.L.…”
mentioning
confidence: 99%